Complications of balloon pulmonary angioplasty for chronic thromboembolic pulmonary disease according to the classification proposed by the 6th world symposium on pulmonary hypertension. (14th October 2021) - Pereira, A R; Cale, R; Ferreira, F; Alegria, S; Sebaiti, D; Martinho, M; Repolho, D; Vitorino, S; Santos, P; Loureiro, M J; Pereira, H
Abstract: Introduction: Balloon pulmonary angioplasty (BPA) is a complex procedure and not risk free. In an attempt to standardize reports of BPA complications in the several centers, a classification of complications was proposed by the task force on chronic thromboembolic hypertension (CTEPH) in the 6th World Symposium on Pulmonary Hypertension (WSPH). Purpose: To determine the prevalence of BPA complications according to the classification of 6th WSPH and to identify its predictors. Methods: Detailed procedural and technical aspects were collected for consecutive patients (pts) with inoperable, residual/recurrent chronic thromboembolic disease, undergoing BPA at a single institution from December/2017 to December/2020. Per procedure logistic regression analysis was used to evaluate the predictive variables for complications. Results: A total of 76 BPA sessions in 15 pts were performed (mean age 63.2±14.0 years; 60.0% women; 86.7% CTEPH). Mean pulmonary artery pressure and pulmonary vascular resistance before the first BPA session were 33.1±13.3 mmHg and 4.8±3.2 woods unit, respectively (73.3% of pts under vasodilator therapy). Femoral access was used for all pts. Mean vessels treated per procedure were 4.3±1.9 (324 vessels in total). Webs, subtotal occlusions, ring-like stenosis and total occlusions were noted in 215 (66.4%), 58 (17.9%), 31 (9.6%) and 20 (6.2%) treated vessels, respectively. We performed 21 pressure-wire-guided sessions (27.6%). Intravascular imaging was used in 6 procedures (7.9%). Average time of fluoroscopy was 60.3±14.0 minutes and volume of contrast 273.0±73.0 mL per session. Procedure-related adverse events occurred in 25.0% of the interventions (27.6% in the first two years vs 16.7% in the last two). Pulmonary artery vascular injuries were noted in 6 BPA vessels (7.9% per procedure and 1.9% per treated vessel): haemoptysis in all, but perforation was only detected angiographically in 3 of them (balloon inflation was performed for 2 distal perforations, and 1 perforation sealed without any intervention). Vascular dissection in distal lesions occurred in 4 cases (5.3%) with no need of transcatheter or surgical procedures. We had 3 lung injuries, all grade 2. None of the pts required oral intubation or mechanical ventilation. Extra-pulmonary complications were illustrated in table. Importantly, there was no peri-procedural death. The occurrence of vascular or lung injuries was 0% in pressure-wire-guided BPA versus 14.5% in non-guided (p=0.098). Multivariate analysis revealed that age (OR 1.05; CI 1.01–1.10; p=0.030) was the only independent predictor of complications. Conclusions: In our experience, BPA can be safely performed in inoperable, residual or recurrent CTEPH or CTED pts, with 25% minor procedural-related complications but no major adverse event. Age was the strongest factor related to the occurrence of complications. FUNDunding Acknowledgement: Type of funding sources: None.